The Return of Decentralization Greek Local Government Response to the COVID-19 Pandemic - Plimakis, Sifis (European Scientific Journal, ESJ, 2023)
The COVID-19 pandemic was one of the greatest crisis faced by humanity. It had a significant negative impact that affected public health, the society, the economy, and the performance of public administration. Although national administrative system’s response to COVID-19 pandemic was set up, the performance and the resilience of strategic management patterns at national and local level was also initiated. This paper focuses on identifying and evaluating the strategies and models adopted by Greek local government to build resilience during the COVID-19 crisis. The results of the research are based on an empirical survey conducted in 27 municipal authorities in Greece, which showed that despite the various government policy initiatives and funding provided during the last decade and the formal introduction of crisis management and resilience focused planning models, urban resilience is downgrading due to the continuation of important implementation and compliance gaps in strategic planning and performance measurement adoption from the municipal authorities and the lack of an effective model of multi-level coordination among policy’s stakeholders.